2006
DOI: 10.1097/01.pcc.0000231946.88688.07
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-induced thrombocytopenia in a pediatric patient receiving extracorporeal membrane oxygenation managed with argatroban???

Abstract: This report documents a pediatric case of HIT type II successfully treated with argatroban, allowing continuation of the ECMO and continuous renal replacement therapy therapy, with resolution of the cutaneous ischemia and thrombocytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Our final literature set (table 1) therefore comprised 34 publications that together described argatroban anticoagulation in 644 patients with varying degrees of renal function and with either suspected, confirmed, or previous HIT (5 prospective studies [10, 25, 29, 31, 32], 3 retrospective studies [22, 34, 35], 15 case reports [36,37,38,39,40,41,42,43,44,45,46, 48, 49]); antithrombin deficiency (1 retrospective study [33], 2 case reports [16, 47]), or neither HIT nor antithrombin deficiency (6 prospective studies [5, 23, 24, 27, 28, 30]). Overall, the data were prospective in 185 patients (70 with suspected, confirmed, or previous HIT), retrospective in 430 patients (80 with antithrombin deficiency and 350 with suspected, confirmed, or previous HIT), and anecdotal in 29 patients (26 with suspected, confirmed, or previous HIT and 2 with antithrombin deficiency).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our final literature set (table 1) therefore comprised 34 publications that together described argatroban anticoagulation in 644 patients with varying degrees of renal function and with either suspected, confirmed, or previous HIT (5 prospective studies [10, 25, 29, 31, 32], 3 retrospective studies [22, 34, 35], 15 case reports [36,37,38,39,40,41,42,43,44,45,46, 48, 49]); antithrombin deficiency (1 retrospective study [33], 2 case reports [16, 47]), or neither HIT nor antithrombin deficiency (6 prospective studies [5, 23, 24, 27, 28, 30]). Overall, the data were prospective in 185 patients (70 with suspected, confirmed, or previous HIT), retrospective in 430 patients (80 with antithrombin deficiency and 350 with suspected, confirmed, or previous HIT), and anecdotal in 29 patients (26 with suspected, confirmed, or previous HIT and 2 with antithrombin deficiency).…”
Section: Resultsmentioning
confidence: 99%
“…No one had systemic thrombosis during hemodialysis; 1 patient had clotting in the dialysis circuit; 1 patient had nonfatal bleeding that was multifactorial in origin. A case report [49] presented a 17-month-old patient with HIT who underwent successful continuous RRT and extracorporeal membrane oxygenation using argatroban anticoagulation. Argatroban doses of 1–2 µg/kg/min supported ACTs of 180– 200 s, and there was no bleeding complication.…”
Section: Resultsmentioning
confidence: 99%
“…There are limited data on their use in children undergoing extracorporeal circulation. 27,30,34 A study comparing heparin and argatroban utilizing sham ECMO circuits demonstrated significantly less thrombin generation in the circuits with argatroban compared to heparin. 35 Although these data are intriguing and point to a potential role for DTI in ECMO, confirmation of this finding is required including clinical trials before DTI can be recommended as alternatives to standard therapy with heparin.…”
Section: Short-acting Agentsmentioning
confidence: 99%
“…For cardiac surgery with cardiopulmonary bypass (CPB), argatroban anticoagulation has been used on occasion 3 . Argatroban has also been used for noncardiac surgery indications and noncardiac surgery, extracorporeal life support 5,6 . However, to the best of our knowledge, there are only four previous case reports detailing argatroban's use in infants (<12 months of age) who survived cardiac surgery utilizing CPB 7–10 …”
Section: Introductionmentioning
confidence: 99%
“…3 Argatroban has also been used for noncardiac surgery indications and noncardiac surgery, extracorporeal life support. 5,6 However, to the best of our knowledge, there are only four previous case reports detailing argatroban's use in infants (<12 months of age) who survived cardiac surgery utilizing CPB. [7][8][9][10] We present an infant with double outlet right ventricle (DORV) and history of a systemic to pulmonary artery shunt (SPAS), protein C deficiency, a methylene-tetra-hydro-folate reductase (MTHFR) gene mutation, and HIT that required CPB for complete repair.…”
Section: Introductionmentioning
confidence: 99%